Training in lockdown: The impact of stringency measures on the Tokyo 2020 Olympic Games - Alfano, V.; Ercolano, S. (International Journal of Sports Science & Coaching, 2023)
Due to COVID-19, the 32nd Olympic Games were postponed temporarily for the first time, apart from those cancelled during the First and Second World Wars. Did the pandemic also affect the results? We aim to understand the impact of stringency measures on athletes` performance in the Olympics. For many athletes, the Olympics are the pinnacle of their careers, and they follow intense training schedules to arrive at the Games in peak physical condition. Stringency measures may have affected their results by making it harder for them to train effectively, to access sports infrastructure, to meet teammates, and more generally to follow an athletic lifestyle. Our quantitative analysis shows that stringency measures had an effect on the number of Olympic medals won, especially in team sports. This is consistent with the idea that stricter non-pharmaceutical interventions made it harder for teams to train together and achieve the necessary chemistry and harmony to succeed in such a competitive event. Furthermore, women were more severely penalized by higher stringency measures than men in team events.